2020
DOI: 10.1037/dev0000899
|View full text |Cite
|
Sign up to set email alerts
|

Piecing together the role of a spatial assembly intervention in preschoolers’ spatial and mathematics learning: Influences of gesture, spatial language, and socioeconomic status.

Abstract: Spatial skills are associated with mathematics skills, but it is unclear if spatial training transfers to mathematics skills for preschoolers, especially from underserved communities. The current study tested (a) whether spatial training benefited preschoolers’ spatial and mathematics skills, (b) if the type of feedback provided during spatial training differentially influenced children’s spatial and mathematics skills, and (c) if the spatial training’s effects varied by socioeconomic status (SES). Preschooler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…Active memory practices promote the consolidation process by challenging one's mind to analyze information. Various studies revealed that children with SLD have poor performance in active memory (Bower et al, 2020). Considering the results of this study and similar investigations, active memory training can alleviate problems in children with SLD.…”
Section: Discussionsupporting
confidence: 78%
“…Active memory practices promote the consolidation process by challenging one's mind to analyze information. Various studies revealed that children with SLD have poor performance in active memory (Bower et al, 2020). Considering the results of this study and similar investigations, active memory training can alleviate problems in children with SLD.…”
Section: Discussionsupporting
confidence: 78%
“…Spatial skills are malleable (e.g., Uttal et al, 2013). Various environmental factors, such as spatial play (e.g., blocks, puzzles) or spatial language (e.g., hearing words about spatial relations), correlate with better spatial skills and also improve spatial skills (e.g., Levine et al, 2012;Verdine et al, 2014a,b;Bower et al, 2020;Casasola et al, 2020). Our findings are in line with the general prior literature as well as with specific studies focusing on spatial language use.…”
Section: Discussionmentioning
confidence: 99%
“…Research supports the benefits of active learning-where children are focused and engaged in the learning process through questioning and reflection-over passive learning where students memorize information (Chi 2009). When they are actively involved in the learning process, children can build spatial skills (Bower et al 2020) and learn properties of shapes (Fisher et al 2013) and new words (Han et al 2010). (ii) Engaging.…”
Section: How Children Learn: Playful Learning Principlesmentioning
confidence: 96%
“…Traditional content includes reading, writing, math, science, social studies, and the arts, but it is also important to recognize "learning to learn" or executive function skills including attention (Duncan et al 2007) and working memory (Nguyen and Duncan 2019) that support children's academic achievement. Content builds on collaboration and communication across the disciplines, including math (Bower et al 2020;Ribner et al 2020); literacy (Ribner et al 2020); science; and social studies (Gonzalez et al 2010). (iv) Critical thinking.…”
Section: What Children Learn: the 6 Cs-a Breadth Of Skills Approachmentioning
confidence: 99%